Dominica : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This Selected Issues paper presents a proposal for the creation of savings funds (SF) for rehabilitation and reconstruction after natural disasters (ND) in Dominica. A Monte Carlo experiment is used to calibrate the size of the SF, based on the distribution of ND fiscal shocks estimated from an empirical fiscal model. ND shocks are identified by controlling for other major sources of shock affecting the cyclical fluctuations of output, and government revenue and expenditure, and by calibrating the probability of ND consistent with their historical frequency. It is concluded that under the parameter calibrations proposed, the SF would be financially sustainable with a low probability of depletion.